A simple phenomenological model for time evolution of social networks. (March 2015) - Jiang, J; Wang, Q A; Li, W; Cai, X
Abstract: Inspired by the maxim "long union divides and long division unites", a phenomenological model with the simplification of real social networks is proposed to explore the evolutionary features of these networks composed of the entities whose behaviors are dominated by two events: union and division. The nodes are endowed with some attributes such as identity, ingredient, richness, age and internal diversity, which determine collectively the evolution in a probabilistic way. Through the local interaction of two events, a stationary state of network is reached as a constant amount of nodes survive with no more event happened in the network, like a situation of tripartite confrontation. Besides, the number of survived nodes and the speed of network evolution can be controlled by two parameters.